Synthesis of Cyclic Carbonates from Epoxides and CO2 under Mild Conditions Using a Simple, Highly Efficient Niobium‐Based Catalyst. Issue 6 (20th February 2013) - Monassier, Antoine; D'Elia, Valerio; Cokoja, Mirza; Dong, Hailin; Pelletier, Jérémie D. A.; Basset, Jean‐Marie; Kühn, Fritz E.
<x xml:space="preserve">Abstract</x> Like a sore thumb: Niobium stands out among neighboring transition metals for its catalytic performance in the synthesis of cyclic carbonates. Readily available NbCl5 is a very efficient catalyst for the preparation of industrially relevant carbonates at ambient temperature, low CO2 pressure, and low concentrations. DMAP=N, N‐dimethylaminopyridine.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>